2018
DOI: 10.3390/toxins10080333
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Properties of the Nephrotoxin Orellanine in Rats

Abstract: Orellanine is a nephrotoxin found in mushrooms of the Cortinarius family. Accidental intake of this substance may cause renal failure. Orellanine is specific for proximal tubular cells and could, therefore, potentially be used as treatment for metastatic renal cancer, which originates from these cells. However, more information is needed about the distribution and elimination of orellanine from the body to understand its potential use for therapy. In this study, 5 mg/kg orellanine (unlabeled and 3H-labeled) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…A combination of animal studies and biopsies taken from poisoned patients have shown that orellanine acts on the proximal tubular cells of the kidney, with a significant degree of selectivity, even over other renal cells. , The selectivity of its uptake is poorly understoodwhile it has been suggested that it enters proximal tubular cells via an active, sodium independent transporter, this has yet to be confirmed or investigated further. It has also been suggested that orellanine is re-absorbed from the urine by a specific renal transporter, as the observed plasma half-life in rats was longer than what would be predicted for a molecule with similar physicochemical properties …”
Section: Identity and Toxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…A combination of animal studies and biopsies taken from poisoned patients have shown that orellanine acts on the proximal tubular cells of the kidney, with a significant degree of selectivity, even over other renal cells. , The selectivity of its uptake is poorly understoodwhile it has been suggested that it enters proximal tubular cells via an active, sodium independent transporter, this has yet to be confirmed or investigated further. It has also been suggested that orellanine is re-absorbed from the urine by a specific renal transporter, as the observed plasma half-life in rats was longer than what would be predicted for a molecule with similar physicochemical properties …”
Section: Identity and Toxicitymentioning
confidence: 99%
“…As a group of compounds, orellanine and its metabolites have several properties that lend themselves to identification and quantification, by liquid chromatographic methods in particular. While orellanine itself lacks a fluorophore, its reduced metabolite orelline produces a distinctive turquoise fluorescence (excitation wavelength 400 nm, emission wavelength 450 nm) ,, and is readily formed under a range of conditions, including when exposed to UV light. , ,,, This can be explained by the reduction of the N -oxides, which enables the necessary electron spin transitions via keto–enol tautomerism, a phenomenon seen across a range of 3,3′-dihydroxy bipyridines , (Figure ). …”
Section: Analysis and Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue of Toxins includes three recent advanced research studies related to bee venoms as potential medicinal therapy in different aspects [1,2,3]. Furthermore, recent advances in bioactive molecules finding from frog skins, mushroom and venom/toxin/immunotoxins for targeted cancer therapy and immunotherapy are discussed [4,5,6,7,8]. The discussion on using novel disease-specific venom-based protein/peptide/toxin along with currently available FDA approved drugs as combinatorial treatment, such as a family of novel types of antimicrobial agents, were also encouraged to be discussed in these contexts.…”
mentioning
confidence: 99%